Reliability Evaluation of Service-Oriented Architecture Systems Considering Fault-Tolerance Designs - Kuan-Li Peng; Chin-Yu Huang (Journal of Applied Mathematics)
Service-oriented architecture (SOA) provides an elastic and automatic way to discover, publish, and compose individual services. SOA enables faster integration of existing software components from different parties, makes fault tolerance (FT) feasible, and is also one of the fundamentals of cloud computing. However, the unpredictable nature of SOA systems introduces new challenges for reliability evaluation, while reliability and dependability have become the basic requirements of enterprise systems. This paper proposes an SOA system reliability model which incorporates three common fault-tolerance strategies. Sensitivity analysis of SOA at both coarse and fine grain levels is also studied, which can be used to efficiently identify the critical parts within the system. Two SOA system scenarios based on real industrial practices are studied. Experimental results show that the proposed SOA model can be used to accurately depict the behavior of SOA systems. Additionally, a sensitivity analysis that quantizes the effects of system structure as well as fault tolerance on the overall reliability is also studied. On the whole, the proposed reliability modeling and analysis framework may help the SOA system service provider to evaluate the overall system reliability effectively and also make smarter improvement plans by focusing resources on enhancing reliability-sensitive parts within the system.